Analisis Kualitas Pelayanan Publik Pada Kantor Desa Kersik Belantian Kecamatan Jelimpo Kabupaten Landak - maulana Filani Rizal (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2022)
This research entitled "Public Perception on Service Making From BRI Sekadau. Therefore, in providing services should be guided by: total customer satisfaction, making quality as the primary goal in service, building quality in a process, applying your satisfaction philosophy is our service purpose, speaking facts, and establishing partnerships both internally and externally. Complaints from the public in the administration of correspondence of various interests have not fulfilled the wishes and expectations of the needs of the community as a consumer. This complaint can not be separated from the increasing public awareness that demanded the improvement of services. Based on the results of research conducted there is a match between the level of performance and the level of importance is equal to 94.17 which means the services provided by has been very good because it is in the range> 85%. The dimension of service that has the highest level of compliance (Tki) is the dimension of Empathy (Emphaty), which is 98.09%, while the service dimension which has the lowest level of conformity is Reliability (Realibility), which is 91.61%. This means that the dimension of Empathy (Emphaty) has a much better performance compared to the other four dimensions.